SISTEM INFORMASI GEOGRAFIS PETA PENYEBARAN COVID-19 DI KOTA BATAM - Syaeful Anas Aklani (Lambung Mangkurat University, 2021)
The development of the Covid-19 virus in Indonesia continues to increase rapidly and according to reports from the Batam City Health Office, the graph of Covid-19 sufferers is increasing day by day, so the Batam city government has difficulty determining which areas are red zones that need to be watched out, so it requires attention. Specifically, the problem is the lack of socialization of referral hospitals or clinics for handling Covid-19 through maps. With the above problems, the authors designed a geographic information system for the map of the spread of Covid-19 in the city of Batam, so it is necessary to map the area for the spread of the Covid-19 virus to find out which areas are vulnerable so that the people of Batam City can access information quickly and precisely. The software development life cycle rapid application development (RAD) method is one that can be used for short and fast map design making it easier to work on the Covid-19 distribution map in a short time. with the information system helping the people of Batam, especially in accessing map data for the spread of Covid-19, which zones need to be watched out for according to the spread of the virus, information on health centers and referral hospitals for handling COVID-19 quickly according to the sub-districts in the city of Batam. Keywords: Covid-19, Google Maps, Maps, Rapid Application DevelopmentPerkembangan virus Covid-19 di Indonesia terus meningkat dengan pesat dan menurut laporan dari dinas kesehatan kota batam semakin meningkat grafik penderita Covid-19 dari hari ke hari, sehingga pemerintah kota Batam kesulitan menentukan daerah mana saja yang berzona merah yang perlu di waspadai sehingga memerlukan perhatian khusus, permasalahan di tambah lagi kurangnya sosialisasi rumah sakit atau klinik puskesmas rujukan untuk penanganan Covid-19 melalui peta. dengan permasalahan diatas maka penulis merancang sistem informasi geografis peta peyebaran Covid-19 di kota batam, sehingga diperlukan adanya pemetaan daerah penyebaran virus Covid-19 untuk mengetahui tingkat wilayah mana saja yang rawan sehingga masyarakat kota batam dapat mengakses informasi dengan cepat dan tepat. metode software development life cycle rapid application development (RAD) salah satu yang dapat digunakan untuk perancangan peta dengan singkat dan cepat sehingga memudahkan dalam pengerjakan peta sebaran Covid-19 dengan waktu yang singkat. dengan adanya sistem informasi membantu masyarakat kota batam khususnya dalam mengakses data peta penyebaran Covid-19, zona mana saja yang perlu di waspadai sesuai penyebaran virus, informasi puskesmas dan rumah sakit rujukan untuk penangan Covid-19 dengan cepat sesuai dengan kecamatan yang ada dikota BatamKata kunci: Covid-19, Google Maps, Peta, Rapid Application Development